Myclinic: location awareness mobile application using geo-fencing / Mohamad Afiq Mohamad Nasir - Mohamad Nasir, Mohamad Afiq (Faculty of Computer and Mathematical Sciences, 2019)
MyClinic is a mobile application that implement location awareness technique by using geo-fencing. Location awareness refers to the devices that can determine their location either passively or actively. At this moment, government clinics patient often wasting their time at the clinics waiting for treatment due to the numbers of patient keep increasing. They also find that it is tough to find and save the nearest government clinics number phone. Therefore, this project has proposed MyClinic application which has been developed to be used at government clinics in Malaysia. By using this application, the user can take queue number using the application when they are in the geo-fencing of the clinics. It also gives a help for the user to contact the nearest government clinic by using this application with the help of Google Places API. The project has been successfully developed. The application also has been evaluated in terms of the waiting time. The results show that the waiting time have been affected by the network coverage used by the user. The average waiting time for 4G network coverage is within 4 seconds. In conclusion, MyClinic can help in providing the queue numbers taking process by mobile phone and help contacting nearest government clinics.